Childhood and adult social conditions and risk of stroke - Grau, Armin J.; Ling, Paul; Urbanek, Christian; Becher, Heiko; Buggle, Florian (Cerebrovascular diseases, 2012)
Background: Socioeconomic conditions may strongly influence the risk of stroke. We tested the hypotheses that indexes of social status in different life periods including childhood are inversely associated with stroke risk and that there is a cumulative effect of social conditions during lifetime on the risk of stroke. Furthermore, we investigated whether social advancement compared to the parental generation is associated with reduced stroke risk. Methods: In a case-control study, we assessed parental professional status, highest school degree, professional education and the last professional activity in 370 consecutive patients with ischemic or hemorrhagic stroke or transient ischemic attack [TIA; age 60.7 ± 12.8 years (mean ± standard deviation); 31.1% women] and 370 age- and sex-matched control subjects randomly selected from the general population of the same area. Results: Higher level of school exams [odds ratio (OR) 0.58, 95% confidence interval (CI) 0.39-0.86], university or polytechnic high school degrees (OR 0.39, 95% CI 0.24-0.63), nonmanual (last or current) professional activity (OR 0.51, 95% CI 0.37-0.71) and father’s nonmanual professional activity (OR 0.64, 95% 0.43-0.97) were associated with a lower risk of stroke/TIA. Adjustment for vascular risk factors including current smoking and alcohol consumption reduced the strength of these associations and rendered them nonsignificant except for university or polytechnic high school degrees (OR 0.49, 95% CI 0.27-0.87). Additional adjustment for regular sports activity further attenuated the association between academic degrees and risk of stroke/TIA (OR 0.56, 95% CI 0.31-1.02). A score summarizing 4 lifetime social indexes was not independently associated with stroke risk (OR 0.67, 95% CI 0.39-1.16). Social advancement as assessed by changes from paternal manual work to nonmanual work in the index generation was more common among control subjects (23.5%) than patients (15.3%; p = 0.0097), but such advancement was not independently associated with stroke/TIA after adjustment for all covariables (OR 0.82, 95% CI 0.50-1.33). Conclusions: Socioeconomic conditions were inversely linked to the risk of stroke/TIA. These associations were strongly influenced by lifestyle factors such as smoking, alcohol consumption and mainly sports activity. Stroke preventive strategies may have a particularly large potential if they focus on such lifestyle habits in socially disadvantaged groups.
Gesehen am 04.05.2018